THE RELATIONSHIP BETWEEN LANGUAGE LEARNING AND MOTIVATION (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
Motivation has a key role in the development of language skills. Teachers can play a significant role in motivating learners to the learning of a second/foreign language. Motivation is an important factor in learning a foreign language which is in influenced by different variables.